Comparison between ultrasound-guided and palpatory localization of the dorsal joint space of the shoulder joint - Stein, Stephan; Weimer, Andreas; Berthold, Svenja; Weimer, Johannes Matthias; Höppchen, Arnold; Tuffs, Christopher; Schmidmaier, Gerhard; Schamberger, Christian T. (Diagnostics, 2024)
Aim of the study: Arthroscopy ranks among the frequently performed interventions in orthopedics. The aim of this study was to compare the palpation technique with the ultrasound technique for locating the dorsal glenohumeral joint space (JS) in shoulder joint punctures. Material and Methods: Participants inexperienced in ultrasound examinations were included. Palpatory and ultrasound finding of the joint space by the participants was performed according to current recommendations and was initially demonstrated by an instructional video. The ideal point (IP) was marked under ultrasound visualization by an experienced ultrasound examinator and shoulder-elbow surgeon. Furthermore, a corridor for a safe puncture was defined. The palpatorily determined point (pdP) was marked by the participants and evaluated by means of a coordinate system. The evaluation of the sonographically determined point (sdP) was performed similarly to that of the palpatory procedure. Results: Fifty-four participants were included in the study, and the mean length of work experience was 6.3 years. On average, participants had performed 16.5 punctures of the shoulder joint and 6.8 arthroscopies of the shoulder joint. The mean experience in performing sonographic examinations of the shoulder was 27.6 examinations. A total of 100 shoulder joints were examined (54 left, 46 right shoulders). The mean deviation from the ideal point (IP) for the palpatory approach was 17.1 mm with a maximum deviation of 59.5 mm; for the sonographic technique, the mean deviation was 10.3 mm (max. 30.2 mm). Overall, 22% of pdPs were within the defined corridor, while 42% of sdPs were within the target corridor. The average difference between palpatory and sonographic approaches was 9.0 mm in favor of the sonographic technique (max. 46.5 mm). A significantly greater deviation (p < 0.001) from the IP was observed with the palpatory approach than with the sonographic approach. Conclusion: Based on the results, the authors recommend ultrasound imaging of the shoulder joint as well as ultrasound-assisted punctures, especially for inexperienced users. Furthermore, training in ultrasound-assisted interventions should be implemented in future training curricula.
Gesehen am 07.01.2025